Экспериментальное изучение влияния плотности населения личинок Culex pipiens (Diptera, Culicidae) на выживаемость продожительность развития и соотношение полов - Валентюк, E.И.; Ермаков, А.А. (Вестник зоологии, 1980)
Increase in the larva hemipopulation density decreases the larvae growth rate and rises their death rate. The male-female raito is insignificantly affected by variation in the larvae density.